WPŁYW ŚWIATA WIRTUALNEGO SECOND LIFE NA ZMIANY W POZIOMIE MOTYWACJI, LĘKU JĘZYKOWEGO I DOŚWIADCZENIA NUDY U STUDENTÓW FILOLOGII ANGIELSKIEJ - Zawodniak, Joanna; Kruk, Mariusz (Neofilolog, 2018)
The first, theoretical, part of the present paper is devoted to the characteristics of the affective variables of motivation, language anxiety and boredom as situated within the framework of complex dynamic systems. The second part discusses results obtained from a six-month research project intended to examine the effect of Second Life on four English philology students’ changes in levels of motivation, language anxiety and boredom. The data, collected via a personal questionnaire, learner diary and evaluation questionnaire, underwent both quantitative and qualitative analysis.